Framing Visual Perception in Terms of Sensorimotor Mapping - Silvano Zipoli Caiani (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
Two contrasting theories, or variants of them, are predominant in the current debate on visual cognition. The standard inferential theory sees perception as a process involving the role of memory, past experiences and semantic abilities, whereas the direct theory sees perception as a connection between the perceiver and the environment that does not recruit internal information processing. In particular, the direct theory has recently been invoked because it would be able to explain the sensorimotor coupling of perception and action in humans and animals without relying on controversial notions such as those of conceptualization and propositional information. This paper aims to show that even an inferential theory of perception has enough resources to account for sensorimotor processes without necessarily involving high level cognitive functions. My claim is that there are genuine instances of sensorimotor inferential processing that do not rely on conceptual structures and propositional knowledge. Several theoretical and empirical arguments are provided to support this statement.
Keywords: inferential theory; direct theory; visual cognition; perception and action; conceptualization; propositional knowledge